1991
DOI: 10.1128/aem.57.11.3361-3366.1991
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of and inhibition by chlorobenzoates in Pseudomonas putida P111

Abstract: Pseudomonas putida Pill was isolated by enrichment culture on 2,5-dichlorobenzoate and was also able to grow on 2-chloro-, 3-chloro-, 4-chloro-, 2,3-dichloro-, 2,4-dichloro-, and 2,3,5-trichlorobenzoates. However, * Corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
3

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 31 publications
(28 reference statements)
4
21
0
3
Order By: Relevance
“…The highperformance liquid chromatography analysis showed no 4-chlorophenol before the acidification (data not shown). The same kind of result was observed by Hernandez et al (12). So, 4-chlorophenol detected would not be a true intermediate metabolite of 4-chlorobiphenyl.…”
Section: Discussionsupporting
confidence: 82%
“…The highperformance liquid chromatography analysis showed no 4-chlorophenol before the acidification (data not shown). The same kind of result was observed by Hernandez et al (12). So, 4-chlorophenol detected would not be a true intermediate metabolite of 4-chlorobiphenyl.…”
Section: Discussionsupporting
confidence: 82%
“…Proposed pathways for aerobic degradation of fluorobenzoates and benzoate (adapted from [218]). 46 2,5-dichloro-and 2,3,5-trichiorobenzoate to chlorocatechols was also reported for a Pseudomonas putida strain [209].…”
Section: Aerobic Degradation Of Halobenzoatesmentioning
confidence: 63%
“…Chlorobenzoatedegrading bacteria were shown frequently to be absent in soils while PCB-co-metabolizing strains were routinely isolated from contaminated soil by the enrichment on biphenyl (Hickey et al 1993). Hernandez et al (1991) isolated Pseudomonas putida P111 which was shown to have the greatest range of chlorobenzoate utilization yet reported. Further studies (Brenner et al 1993) revealed the presence of the gene for ortho-chlorobenzoate-1,2-dioxygenase (OCBD) on transmissible plasmid pPB111 which was shown to be responsible for the extraordinarily broad degradation activities of this strain.…”
Section: Introductionmentioning
confidence: 99%